the Approach Solution Numeric for Mathematical Models Celebrity Worship Behavior Among K-Pop Fans Based Wisdom Local in South Sulawesi Using Runge- Kutta method Order 6: bahasi Inggris - Mulyaningrum, Dwidary; minggi, ilham; Side, syafruddin; Yusuf Sainon Andi Pandjajangi, Andi Muhammad Ridho (Journal of Mathematics, Computations and Statistics, 2024)
Studies This explore the mathematical model of SFR with use run kutta order 6 that catches rate Behavior Worship Celebrities among​ fan loyal K-Pop. Main data obtained through direct questionnaire​ taken from communities in South Sulawesi Province , provide outlook about rhythm Behavior Worship Celebrities among​ K-Pop lovers . Research This aiming For to study phenomenon idolization K-Pop celebrities among fans in South Sulawesi through approach solution numerical . Using the SFR mathematical model and the Runge- Kutta method Order 6, results simulation show that K-Pop idolization in the region This Enough significant , influenced by social media as well as factor culture and social local . Data shows existence decline amount vulnerable fans​ to addicted to K-Pop, but fluctuation behavior addiction and decline number recovery still become attention . Research This highlight importance more intervention​ effective , such as therapy and support social , for overcome impact negative from idolization celebrity . Findings This also provides outlook valuable for development strategy in handle phenomenon idolization celebrities who continue develop in the future.